2022
DOI: 10.1371/journal.pone.0268692
|View full text |Cite
|
Sign up to set email alerts
|

Development and implementation of a simple and rapid extraction-free saliva SARS-CoV-2 RT-LAMP workflow for workplace surveillance

Abstract: Effective management of the COVID-19 pandemic requires widespread and frequent testing of the population for SARS-CoV-2 infection. Saliva has emerged as an attractive alternative to nasopharyngeal samples for surveillance testing as it does not require specialized personnel or materials for its collection and can be easily provided by the patient. We have developed a simple, fast, and sensitive saliva-based testing workflow that requires minimal sample treatment and equipment. After sample inactivation, RNA is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 60 publications
1
15
0
Order By: Relevance
“…As a demonstration of PAPS-based detection, we applied it for detecting synthetic SARS-CoV-2 RNA by RT-LAMP. We performed 24 reactions with input of approximately 10 copies of viral RNA per reaction, which is below the limit of detection of a commercially available kit based on a pH-dependent dye (~50 copies, SARS-CoV-2 Rapid Colorimetric LAMP Assay Kit, NEB #E2019 42 , 43 ), in order to observe both positive and negative reactions (Fig. 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…As a demonstration of PAPS-based detection, we applied it for detecting synthetic SARS-CoV-2 RNA by RT-LAMP. We performed 24 reactions with input of approximately 10 copies of viral RNA per reaction, which is below the limit of detection of a commercially available kit based on a pH-dependent dye (~50 copies, SARS-CoV-2 Rapid Colorimetric LAMP Assay Kit, NEB #E2019 42 , 43 ), in order to observe both positive and negative reactions (Fig. 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, mpox DNA can be found in the saliva of infected cases by using qPCR [ 43 ]. Previous reports showed that unpurified SARS-CoV-2 in saliva samples can be detected with no RNA extraction step via a RT-LAMP assay [ 44 , 45 ]. As the reaction temperature of our LAMP assay is 65 °C and mpox virus can be inactivated at 60 °C in under 15 min [ 46 ], this LAMP assay can theoretically be used to detect mpox from crude clinical saliva samples without prior DNA extraction.…”
Section: Discussionmentioning
confidence: 99%
“…For clinical samples, RNA extractions were performed as described ( 22 ) following NEB’s protocol for RNA extraction from saliva utilizing the Monarch Total RNA Miniprep Kit (T2010). The final total RNA was eluted in either 50 or 100 μl of nuclease free water prior to storage at –20°C for less than 1 week or –80°C for long term storage.…”
Section: Methodsmentioning
confidence: 99%